Assessment of the Factors of Insufficient Effectiveness of Treatment of Inflammatory Genital Disease Caused by Chlamydia - Rudenko, A.V.; Romashchenko, O.V.; Romanenko, A.M.; Grygorenko, V.M.; Yakovenko, L.F.; Chabanov, P.V.; Ugarov, V.Yu.; Руденко, А.В.; Ромащенко, О.В.; Романенко, А.М.; Григоренко, В.М.; Яковенко, Л.Ф.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
The prevalence of the latent course of genital inflammatory disease caused by chlamydia and its untimely diagnosis lead to an increase in the frequency of etiologically unidentified inflammatory processes and the application of unjustified treatment tactics. The aim of the research was to identify the causes of insufficient effectiveness of traditional treatment methods for genital inflammatory disease caused by chlamydial infection in women and men. Methods. Gynecological, paraclinical, and microbiological examinations were conducted on 170 women aged 19 to 35 years with chronic genital inflammatory disease (with an inflammation duration ranging from 2 to 12 years), which was complicated by infertility in 48 (28.2%) patients. Parallel examinations were conducted on 165 men aged 20 to 42 years with chronic urethritis and/or prostatitis of chlamydial etiology (with a disease duration ranging from 3 to 11 years). In the group of women (24 examined) with chronic genital inflammatory disease of chlamydial etiology, hospitalized for surgical treatment of tubal infertility, microbiological and morphological studies of surgical material fragments were conducted. Additionally, the concentration of doxycycline hydrochloride in the tissues of the fallopian tubes, blood, and urine was determined after oral administration of the drug on the 3rd, 6th, and 9th days. Similarly, in men with chronic urethritis of chlamydial etiology, the concentration of doxycycline hydrochloride in epithelial cells of the urethral mucosa, blood, and urine was determined. Results. The study established that the insufficient effectiveness of treatment for chronic genital inflammatory disease caused by chlamydia in both women and men is due to the absence of the necessary minimum inhibitory concentrations of antibacterial drugs (tetracycline group) when administered orally to suppress chlamydia at the site of infection. Additionally, the degree of anatomic and functional changes in the fallopian tubes (their sclerotic destruction due to chlamydial infection) in women and the urethral epithelium in men contribute to the treatment ineffectiveness. Conclusions. One of the primary factors contributing to the insufficient effectiveness of conservative treatment methods for genital inflammatory disease of chlamydial etiology is the untimely administration of treatment. At this stage, anatomical and functional changes in the pelvic organs become irreversible. Morphological changes in the tissues of the fallopian tubes due to chlamydial infection are characterized by the development of sclerotic destruction of the organ against the backdrop of disrupted intra-organ blood circulation. This explains the insufficient effectiveness of traditional anti-inflammatory treatment regimens for chronic salpingitis of this etiology with tetracycline antibiotics when administered orally in the later stages of the disease.